The Effect of the Project-Based Learning (PJBL) Method on Microsoft Word Learning Skills in Grade 10 Students at Senior High School 4 North Bengkulu - Alkes Solindar; Asnawati Asnawati; Hermawansa Hermawansa (Universitas Dehasen Bengkulu, 2026)
This study aims to determine the effect of the Project Based Learning (PjBL) method on Microsoft Word learning skills in class X students of SMA Negeri 4 Bengkulu Utara. The study used a quantitative approach with the Quasi Experimental Design method of the Nonequivalent Control Group Design type. The research sample consisted of 72 students divided into experimental and control classes. Data were collected through pretest and posttest tests, then analyzed using normality, homogeneity, and t-test tests. The results showed that the average value of the control class increased from 61.67 to 67.94 or by 6.27 points, while the average value of the experimental class increased from 63.31 to 81.08 or by 17.77 points. This indicates that the increase in learning outcomes in the experimental class was higher than the control class after the implementation of the Project Based Learning (PjBL) method. The results of the hypothesis test showed a significance value of 0.001 < 0.05 and a α value of 7.020 > α of 2.030, thus H2 is rejected and H3 is accepted. Therefore, it can be concluded that the use of the Project-Based Learning method has a significant effect on student learning outcomes. Furthermore, improvements in student skills and learning outcomes are influenced by several factors, namely learning methods, student activeness, learning motivation, and the role of the teacher.